Strategic empowerment: Japan's evolving policy toward Southeast Asia from the 2010s - Koga, Kei (2024)
How has Japan developed its Southeast Asian strategy in the context of the intensifying US-China rivalry since the 2010s? This article argues that the rapidly changing strategic environment brought about by the assertive rise of China prompted Japan to adopt a new strategic vision that went beyond the traditional geographical focus on East Asia. Japan has gradually positioned Southeast Asia as one of the most important strategic theatres in the Indo-Pacific. Utilising its existing economic and diplomatic leverage in Southeast Asia, Japan has been pursuing various types of capacity-building strategies to empower Southeast Asian states and ASEAN to maintain regional autonomy, which the author calls “strategic empowerment”. While Japan has engaged in similar cooperative activities in the past, it has renewed its commitment through three main means: building a strategic partnership in Southeast Asia; promoting international rules, norms and values; and strengthening ASEAN-led institutions.